Novel ball-type homo- and hetero-dinuclear phthalocyanines with four 1,1 '-methylenedinaphthalen-2-ol bridges: Synthesis and characterization, electrical and gas sensing properties and electrocatalytic performance towards oxygen reduction - ÖZKAYA, ALİ RIZA; ODABAŞ, ZAFER (ELSEVIER SCIENCE SA, 2010)
The new mono-nuclear Fe(II) phthalocyanine 2 and ball-type homo-dinuclear Fe(II)-Fe(II) phthalocyanine 3 were synthesized from the corresponding 4,4'4-[1,1'-methylenebis-(naphthalene-2,1-diyl)]bis(oxy)diphthalonitrile 1, and then ball-type hetero-dinuclear Fe(II)-Co(II) phthalocyanine 4 was synthesized from 2. The novel compounds have been characterized by elemental analysis, UV/vis, IR and MALDI-TOF mass spectroscopies. Electrocatalytic activity of the high-surface area carbon, Vulcan XC-72R (VC) and Nation (NI) supported complexes towards oxygen reduction was investigated and compared by surface cyclic voltammetry and rotating ring-disk electrode experiments in acidic medium. The VC/Nf/2 and especially VC/Nf/3 modified glassy carbon electrodes showed high catalytic performance, producing water as the main product through the direct four-electron path. A.c. and d.c. measurements were performed on spin coated 2-4 films as a function of temperature (290-436 K). The d.c. results showed an activated conductivity dependence on temperature. The a.c. results gave a temperature dependent frequency exponent s. Gas sensing properties of the films for the volatile organic compounds (VOCs) (toluene, chloroform, ethanol and carbontetrachloride) were also investigated in the temperature range from 290 to 436K. It was observed that the operating temperature had a considerable effect on sensing characteristics of 3 but not 4. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ball-type; Homo-hetero dinuclear; Bisphthalocyanine; Spectroelectrochemistry; A.c. conductivity; Gas sensing; ELECTROCHEMICAL PROPERTIES; HYDROGEN-PEROXIDE; COBALT PHTHALOCYANINES; CATALYTIC-REDUCTION; CATHODIC REDUCTION; THIN-FILMS; METAL-FREE; ELECTROREDUCTION; WATER; STABILITY